2017
DOI: 10.1002/hbm.23894
|View full text |Cite
|
Sign up to set email alerts
|

Validation of T1w‐based segmentations of white matter hyperintensity volumes in large‐scale datasets of aging

Abstract: Our results suggest that while T2w/PD and FLAIR provide more accurate estimates of the true WMHLs, T1w-Only segmentations can still provide estimates that hold strong correlations with the actual WMHLs, age, and performance on various cognitive/clinical scales, giving added value to datasets where T2w/PD or FLAIR are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

7
2

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 42 publications
7
84
0
1
Order By: Relevance
“…Concatenating the two transformations, the other contrasts were also registered to the ADNI template. Using a previously validated automatic WMH segmentation technique and a library of manual segmentations from ADNI dataset, WMHs were segmented for all longitudinal timepoints (Dadar et al, 2018;Dadar, Maranzano, et al, 2017;Dadar, Pascoal, et al, 2017). Quality of segmentations was assessed and verified by an expert (MD).…”
Section: Mri Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Concatenating the two transformations, the other contrasts were also registered to the ADNI template. Using a previously validated automatic WMH segmentation technique and a library of manual segmentations from ADNI dataset, WMHs were segmented for all longitudinal timepoints (Dadar et al, 2018;Dadar, Maranzano, et al, 2017;Dadar, Pascoal, et al, 2017). Quality of segmentations was assessed and verified by an expert (MD).…”
Section: Mri Processingmentioning
confidence: 99%
“…WMHs that result from small vessel disease (SVD) have been associated with vascular risk factors, like hypertension (Shim et al, 2015). WMH load has been associated with AD pathology (Alosco et al, 2018;Dadar et al, 2018), and a relationship between SVD and WMH lesions in AD has been reported in other studies (Shim et al, 2015). WMHs of presumed vascular origin have also been associated with NPS in various populations, including AD (Berlow et al, 2010;Dadar, Maranzano, et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…One of the major challenges when performing tissue classification on aging subjects or individuals with neurodegenerative diseases is the presence of white matter hyperintensities (WMHs). WMHs are areas of increased signal on T2-weighed and FLAIR MRI sequences, which appear as hypointense on T1w images (Dadar et al, 2018b). These hypointense WMH regions can present with a similar intensity profile to the gray matter in T1w images and can be segmented as GM by tissue classification methods that are solely or highly dependent on image intensities.…”
Section: Introductionmentioning
confidence: 99%
“…The image processing and WMH segmentation pipelines used in this study have been designed to process data from multi-center studies, are able to control biases due to multi-site MRI scanning (i.e. differences in acquisition parameters), and have been previously applied successfully to a number of multi-site projects [51][52][53] . The WMH segmentation pipeline has been trained and extensively validated on data from multiple scanners and different acquisition parameters to ensure inter-site and inter-scanner generalizability 26 .…”
Section: Regardless Of Etiology Prevention and Treatment Of Vascularmentioning
confidence: 99%